Lower Trapezius Transfer for Patients With Brachial Plexus Injury - Crepaldi, Bruno E. (Hand (N Y), 2017)
Background: Brachial plexus injury is a complex entity that often results in partial recovery. Most studies to date have focused on improving shoulder abduction. However, a recent technique has been outlined—one that transfers the lower trapezius to improve the external rotation of the shoulder. The primary objective of this study was to evaluate the gains in external rotation of the shoulder in patients who have undergone transfer of the lower trapezius; secondarily, we assessed the range of motion in the elbow and shoulder joints, as well as the muscle strength and quality of life. Methods: This article presents a prospective cohort study of 10 patients who underwent transfer of the lower trapezius. During the preoperative period and at 6 months after the operation, both active and passive goniometric measurements were assessed, as were muscle strength, Mallet’s classification, and patients’ responses to the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. Results: External rotation exhibited an improvement of 17° in the active range of motion and 14° the passive range, which was not statistically significant. Flexion and active abduction of the shoulder, as well as the responses to the DASH, showed positive results. The Mallet’s classification and muscle strength measurement results were not significant. Conclusions: The procedure might be an alternative for restoration of shoulder function and glenohumeral stabilization and mainly to improve quality of life. However, additional studies are required to define and refine this surgical technique.